Transactional Conversation Analysis in Little Abid Stories or Elementary School Students - Windy Apriliani (Mitra Palupi, 2023)
Background: Children's stories are one of the works of children's literature. Children's literature is literature that is read to children. The content of children's literature is determined by the level of intellectual and emotional development of the child. Purpose: Study this is intended for analyzing conversation transactional which is involved in conversation between characters in story Little Abid. Design and methods: This research use a descriptive-qualitative research method, where this research tries to describe phenomena related to the experiences studied, such as behavior, perceptions, motivation, and so on in a holistic manner. Results: The results of this research shown that the conversations found in Little Abid's book consist of 80% complementary conversations, 0% cross conversations, and 20% hidden conversations. Complementary transactions are complementary events occurring between the same two ego states (attitudes) and can occur between two different but complementary ego states (attitudes). Cross transactions, namely transactions occur when messages sent by the ego state do not receive the correct response or do not receive the response expected by the messenger (communicator). Hidden transactions are complex events involving two or more ego states.